Silver Diamine Fluoride pada Pencegahan Early Childhood Caries: Literature Review - Lasmi Dewi Nurnaini; Septriyani Kaswindiarti; Arin Oktaviani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
The prevalence of caries among toddlers in Indonesia was about 81.5%. The type of caries that often occurs among toddlers was Early Childhood Caries (ECC). ECC was a condition where there was one or more tooth decay, the main cause was consuming milk or sugary drinks using a bottle until fall asleep too often which not balanced by oral hygiene maintenances. ECC could be prevented by the treatment of topical application of fluor. One of the preventive agents for topical application of fluor was Silver Diamine Fluoride (SDF). SDF was an invisible solution contains fluor ions and silver ions. SDF could inhibit the demineralization of hard tissues of teeth and carbohydrate metabolism by cariogenic bacteria into acids to prevent caries. The purpose of this study was to evaluate and review Silver Diamine Fluoride as a preventive agent of Early Childhood Caries. We searched all the published literature from PubMed, Google Scholar, and Scopus. The review for 16 articles starts from May 2021 until July 2021. Keywords used were “Silver Diamine Fluoride”, “Early Childhood Caries”, “Fluoride”, and “Early Childhood Caries Prevention”, with their combinations. The conclusion of this study was Silver Diamine Fluoride rated as the most effective preventing agent to Early Childhood Caries prevention.